Mechanistic Multiphysics Optimization of Catalyst Layers for High Performance PEM Fuel Cells - Sa′ed Rawashdea (Emerging Science Journal, 2026)
The work set out to optimize the catalyst layer (CL) structure of proton exchange membrane fuel cells (PEMFCs) to maximize electrochemical performance, transport efficiency, and durability simultaneously. The coupled effects of platinum loading distribution, ionomer pathways, and porous microstructure on charge transport, oxygen diffusion, water management, and electrochemical kinetics are investigated through the development of a mechanistic multiphysics modeling framework. The model combines mass and charge conservation, Butler–Volmer reaction kinetics, and effective transport formulations to enable systematic comparison between a standard reference CL and three successively optimized architectures. The findings indicate that the optimized CL designs provide clear improvements in power density, voltage stability, oxygen transport, and electrochemically active surface utilization, while exhibiting lower ohmic losses and reduced transport resistance. Quantitative comparison with experimental data shows that the predictive accuracy improves significantly, with the root mean square error decreasing to 2.7 mAcm⁻² and the coefficient of determination increasing to 0.997 for the most developed design. Moreover, degradation-sensitive aspects, such as platinum loss and interfacial instability, are noticeably alleviated through controlled microstructural design. The main contribution of this work lies in integrating multi-parameter optimization of the catalyst layer architecture within a single mechanistic framework, offering a scalable and robust route toward high-performance.